2016
DOI: 10.1371/journal.pone.0167396
|View full text |Cite
|
Sign up to set email alerts
|

ERP Correlates of Encoding Success and Encoding Selectivity in Attention Switching

Abstract: Long-term memory encoding depends critically on effective processing of incoming information. The degree to which participants engage in effective encoding can be indexed in electroencephalographic (EEG) data by studying event-related potential (ERP) subsequent memory effects. The current study investigated ERP correlates of memory success operationalised with two different measures—memory selectivity and global memory—to assess whether previously observed ERP subsequent memory effects reflect focused encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…Thus, it is likely that participants accepted a certain degree of noise in the consistent categories (based on their experience of the same level of noise on day 1), but in the inconsistent conditions, they were able to recognise that the change in locations could not only be explained by noise, and thus these new locations elicited an increased surprise signal, evident in a larger P3a. This finding of increased P3a amplitude is consistent with the idea that frontal areas are recruited in the face of novel, unexpected stimuli (Soltani & Knight, 2000), that attract attention, which again might aid later memory (Richter & Yeung, 2016). Importantly, in the current study the source of this novelty or surprise signal is solely based on a consolidated memory schema, and not on recently encountered information.…”
Section: Pe and P3supporting
confidence: 90%
See 2 more Smart Citations
“…Thus, it is likely that participants accepted a certain degree of noise in the consistent categories (based on their experience of the same level of noise on day 1), but in the inconsistent conditions, they were able to recognise that the change in locations could not only be explained by noise, and thus these new locations elicited an increased surprise signal, evident in a larger P3a. This finding of increased P3a amplitude is consistent with the idea that frontal areas are recruited in the face of novel, unexpected stimuli (Soltani & Knight, 2000), that attract attention, which again might aid later memory (Richter & Yeung, 2016). Importantly, in the current study the source of this novelty or surprise signal is solely based on a consolidated memory schema, and not on recently encountered information.…”
Section: Pe and P3supporting
confidence: 90%
“…The EEG analysis focused on two clusters of interest: the fronto-central and centro-parietal electrodes. These locations had been shown to display beliefupdating effects (Bennett et al, 2015;Jepma et al, 2018Jepma et al, , 2016Kolossa et al, 2015), in previous studies, and have displayed differential involvement in subsequent memory effects (Richter & Yeung, 2016). In a first step, I tested the prediction that the P3 should be more pronounced in the inconsistent than the consistent condition during day 2 learning.…”
Section: Larger P3s For the Inconsistent Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For these later N2/P3 attentional components, analysis focused on more frontocentral electrodes (Cz, Fz) given the topography of post-perceptual attentional effects previously observed in the literature [32,36,46,50]. Mean amplitudes of the frontal slow wave were calculated across a cluster of frontal electrodes (Fz, FP1, FP2) during a time window ranging from 450-750ms based on the timing and topography of prior subsequent memory effects observed in the literature [47][48][49][50][51][52][53][54].…”
Section: Eeg Data Analysismentioning
confidence: 99%
“…Electrophysiological studies have identified a more sustained frontal slow wave (FSW) occurring later in time (>500ms after stimulus presentation) that predicts whether or not a stimulus will be later remembered or forgotten (subsequent memory) [45][46][47]. This ERP subsequent memory effect is most commonly observed over frontal electrodes in task contexts that strengthen memory encoding (e.g., deep vs. shallow processing, semantic vs. non-semantic classification) and has been linked to more elaborative, frontally-mediated cognitive processing that leads to the formation of a more durable memory trace [47][48][49][50][51][52][53][54]. Although there has been little research into the effects of temporal orienting on electrophysiological responses occurring during this later time window, modulations of this more sustained frontal response may be particularly relevant to effective memory encoding.…”
Section: Introductionmentioning
confidence: 99%